Pencegahan Covid-19 Dalam Tinjauan Ushul Fiqh dan Fikih - Slamet Arofik (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
The prevention of Covid-19 launched by the Indonesian government through the implementation of health protocols (Prokes) strictly does not conflict with Islamic sharia. The Indonesian government's appeal for people not to leave their homes, not to hold Friday prayers and to cancel Eid prayers, Eid al-Adha, not to hold parties, not to hold ta'lim councils and not to allow crowds and always wear masks even in mosques and when performing prayers, if analyzed using ushul fiqh knowledge, especially in the review of مقاصد الشريعة, The theory of Rukhshah and Takhfif can be justified and does not violate Islamic sharia. By not crowding in the form of worship or others is the same as having saved themselves and people from the possibility of being exposed to the virus. This is by the purpose of Islamic sharia in the form of حفظ النفس. Similarly, the prohibition of performing Friday prayers, Hari Raya prayers and congregations in mosques also does not violate Islamic sharia because it is the same as taking Rukhshah and Takhfif in the form of تخفيف إسقاط.